Erinomainen sammalopas maastoon - Hotanen, Juha-Pekka (Metsäntutkimuslaitos, 2013)
Kirja: Jukka Laine, Tapani Sallantaus, Kimmo Syrjänen & Harri Vasander 2013. Sata sammalta. Metsäkustannus Oy. 144 s. ISBN 978-952-6612-13-3.
Kirja-arvostelu
Keywords: kivennäismaa; lehtisammalet; turvemaa